PRÓBA POROZUMIENIA POLSKO-CZECHOSŁOWACKIEGO NA TLE DZIAŁALNOŚCI KLUBU CZESKO-POLSKIEGO W MORAWSKIEJ OSTRAWIE W LATACH 1929-1934 - Dariusz Miszewski (In Gremium. Studies in History, Culture and Politics, 2019)
ATTEMPTS AT POLISH-CZECHOSLOVAK SETTLEMENT AND THE ACTIVITY OF THE POLISH-CZECH CLUB IN MORAVIAN OSTRAVA OVER THE PERIOD OF 1929-1934.The Polish-Czechoslovak tensions of 1918-1920 stemmed from the dispute over the Duchy of Cieszyn, thedistrict of Spisz, and the district of Orawa. The settlement, imposed by the Council of Ambassadors onJuly 28, 1920, harmed Poland. The Poles in the Duchy of Cieszyn became a minority in Czechoslovakiawhich wanted to assimilate them. The Poles in Zaolzie demanded an unflinching policy towards Prague.The Polish authorities only supported them within the scope of the Czechoslovak law. That situationchanged in 1934. The Polish Ministry of Foreign Affairs supported Polish-Czech clubs, including the onein Moravian Ostrava, established in 1929, working on the improvement of the Polish-Czech relationshipsin Zaolzie. Prague’s anti-Polish policy was not changed by the Polish-Czech clubs – nor by the participationof Polish parliamentarians in government coalitions over the period of 1925-1934. After signing thePolish-German Pact of Non-aggression, Poland tried to make Czechoslovakia change its policy towardsthe Polish minority. The German minority’s demand for autonomy made it announce – in February of1937 – its nationalities’ relations improvement declaration. It promised to satisfy the Polish minority’srequirements in late July 938, though its independence was under threat. Prague and Warsaw failed toreach any settlement over the annexation of Zaolzie by Poland in 1938.